Business driven technology - Stephen Haag (McGraw-Hill Irwin, 2008)
BDT takes a business-first approach, starting each chapter by explaining the value of a business initiative and then detailing the technology that enables the initiative. This revolutionary approach instantly demonstrates the why' to business students without boring them with the how'. The adaptive chapter/plug-in organization allows the instructor to adjust content according to their business or technical preferences